(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2016)
The Defence in Depth concept provides a major contribution to the safety philosophy of irradiation facilities. But problems occur when somebody tries to understand or analyse a safety system or develop a new one because there is a lack of practical examples in Safety Series 107 or other IAEA (International Atomic Energy Agency) publications for irradiation facilities. This paper tries to fill this lack of information by providing a series of practical examples and explanations about Defence in Depth concepts